Innovations in water quality monitoring and management in Africa: towards developing an African Water Quality Program (AWaQ) - Mukuyu, Patience; Warner, S.; Chapman, D. V.; Jayathilake, Nilanthi; Dickens, Chris; Mateo-Sagasta, Javier (International Water Management Institute, 2024)
The African Ministers’ Council on Water (AMCOW) Secretariat committed to design and implement an African Water Quality Program (AWaQ) in its Strategic Operational Plan (2020-2024) considering the guiding frameworks it uses such as the Africa Water Vision 2025, United Nations Sustainable Development Goals (SDGs), and the African Union Agenda 2063: The Africa We Want. AMCOW reached out to the International Water Management Institute (IWMI) to support the development of such a program.